2017
DOI: 10.1159/000484298
|View full text |Cite
|
Sign up to set email alerts
|

The Intracranial Aneurysm Gene THSD1 Connects Endosome Dynamics to Nascent Focal Adhesion Assembly

Abstract: Background/Aims: We recently discovered that harmful variants in THSD1 (Thrombospondin type-1 domain-containing protein 1) likely cause intracranial aneurysm and subarachnoid hemorrhage in a subset of both familial and sporadic patients with supporting evidence from two vertebrate models. The current study seeks to elucidate how THSD1 and patientidentified variants function molecularly in focal adhesions. Methods: Co-immunostaining and co-immunoprecipitation were performed to define THSD1 subcellular localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…This distinct variant locations might be the reason for the variable phenotype, given that all heterozygous family members including the elderly as we mentioned earlier are healthy with no record of any cerebrovascular incidents. Rui and colleagues have recently reported that THSD‐1 protein interacts with nascent focal adhesion proteins in extracellular matrix and enhances the formation of a multimeric molecule of the scaffold proteins talin, vinculin and focal adhesion kinase (Figure f) that enhance nascent adhesions formation (Rui et al, ). It appears that these interactions are affected by pathogenic missense variants in intracellular domains as shown in the co‐immunoprecipitation experiments by Rui and co‐workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinct variant locations might be the reason for the variable phenotype, given that all heterozygous family members including the elderly as we mentioned earlier are healthy with no record of any cerebrovascular incidents. Rui and colleagues have recently reported that THSD‐1 protein interacts with nascent focal adhesion proteins in extracellular matrix and enhances the formation of a multimeric molecule of the scaffold proteins talin, vinculin and focal adhesion kinase (Figure f) that enhance nascent adhesions formation (Rui et al, ). It appears that these interactions are affected by pathogenic missense variants in intracellular domains as shown in the co‐immunoprecipitation experiments by Rui and co‐workers.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that these interactions are affected by pathogenic missense variants in intracellular domains as shown in the co‐immunoprecipitation experiments by Rui and co‐workers. However, due to the truncation effect of the variant p.Arg450Ter they were not able to coimmunoprecipitate the mutant protein with any of the scaffold proteins (Rui et al, ). We predict that the truncated protein in our patients will similarly fail to interact with talin and other scaffold proteins affecting the integrin‐extracellular matrix interactions in blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…THSD1 is downregulated in A549 cells and other cancer cell lines, and may function as a tumor suppressor, but its role in cancer and interaction with other genes is not well understood [42]. However, THSD1 has recently been shown to form a protein complex with focal adhesion kinase (FAK), talin, and vinculin, where its role is to promote talin binding to FAK and functions in normal cell adhesion formation and attachment [43]. Therefore, our data suggests that unlike cisplatin, phenanthriplatin treatment might act to prevent the action of THSD1 in some cancers eliminating its role as a tumor suppressor, but the reason for the distinct action of the monofunctional complex compared to cisplatin on THSD1 is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Full length myc‐tagged ZO‐1 and FLAG‐tagged ZO‐2 are available from Addgene (#30317 and # 27415, respectively). The PDZ2 domain of ZO‐1 (nucleotide 514–753) was subcloned into pCMV5 by standard PCR protocol and verified by Sanger sequencing as we previously performed (Rui et al, ).…”
Section: Methodsmentioning
confidence: 99%